Investigating the influence of using smart devices on the ocular accommodative response - Buckhurst, Phillip J; Abdul Rahim, Muhammad Afzam Shah; Purslow, Christine; Buckhurst, Hetal D (IOVS, 2018)
Purpose : Despite the ubiquity of smart devices little is known about their eect on the ocular accommodative response (AR). Given the signicant variation in the display specications of smart devices it is likely that the AR varies between devices. The study rstly examines how AR varies when viewing standardised targets on dierent smart devices and secondly examines the eect of varying target designs on AR. Methods : In this prospective, repeated measures study AR was investigated during two separate experiments utilizing the same protocol. For the rst experiment, evaluation of AR was preformed when participants viewed a single near target (veranda N5 letters) on three dierent platforms (paper, smartphone and smartwatch). During the second experiment participants viewed three dierent targets (Maltese cross, N5 letters and N20 letters) on a single platform. AR was recorded in real time using the WAM-5500 (Grand Seiko Co. Ltd., Hiroshima, Japan) with a badal lens system. The platforms were mounted on a motorised ipper system allowing accommodation demand to be altered between 0 and 3 dioptres. AR metrics were derived using sigmoidal regression curves from the accommodative response stimulus curve. Results : Fifty-eight participants (26 males) with a median age of 21 years (Q =19 and Q =26) were assessed. Accommodative lag was reduced when subjects viewed the target on the smartwatch when compared to the paper (Z=2.765,p=0.017) and smartphone 1 3  (Z=2.956,p=0.009). Accommodative latency was slower with both the smartphone (Z=-4.215, p<0.0005) and smartwatch (Z=-4.496, p<0.0005) relative to the paper platform. Accommodative lag was reduced when viewing the N5 letters in comparison with the N20 letters (Z=-2.670, p=0.023) and Maltese cross (Z=3.623, p=0.001). Accommodative latency was faster with the N20 letters (Z=2.435, p=0.045) relative to the N5 target. Conclusions : The results from this study demonstrated dierences in AR when viewing a letter target on paper, smartphone and smartwatch. Furthermore, the type of target that is displayed on a smartphone is shown to inuence both accommodative lag and latency. This is an abstract that was submitted for the 2018 ARVO Annual Meeting, held in Honolulu, Hawaii, April 29 - May 3, 2018.